The Concept Of Coordination Reform Between Polri Institutions And The Public Prosecutor's Office In Pre-Prosecution - Dani Durahman; Maryadi Wijaya (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
The purpose of this study is to produce a concept so that coordination between the prosecutor's office and the police can run well so that the pre-prosecution process does not hinder the law enforcement process, because, currently, the pre-prosecution can take a long time due to the back and forth of cases. If this happens, back-and-forth examination of case files becomes unnecessary or minimal, because investigators and public prosecutors already have aligned views and needs for proof. So that in carrying out an investigation, the two can complement each other, there is no need to wait until the end of the investigation process which is only limited to 14 days. Conceptually, ideal relations between public prosecutors and investigators can be carried out if the inter-subsystems are not limited by sub-system partitions (functional differentiation). There needs to be a regulation in the Criminal Procedure Code regarding the limit for returning case files from the prosecutor's office to the police three to four times the return of case files after exceeding the limit, the prosecutor must take a stand regarding the case